Frem1 activity is regulated by Sonic hedgehog signaling in the cranial neural crest mesenchyme during midfacial morphogenesis. Issue 4 (19th December 2022) - McLaughlin, Matthew T.; Sun, Miranda R.; Beames, Tyler G.; Steward, Austin C.; Theisen, Joshua W. M.; Chung, Hannah M.; Everson, Joshua L.; Moskowitz, Ivan P.; Sheets, Michael D.; Lipinski, Robert J.
Abstract: Background: Frem1 has been linked to human face shape variation, dysmorphology, and malformation, but little is known about its regulation and biological role in facial development. Results: During midfacial morphogenesis in mice, we observed Frem1 expression in the embryonic growth centers that form the median upper lip, nose, and palate. Expansive spatial gradients of Frem1 expression in the cranial neural crest cell (cNCC) mesenchyme of these tissues suggested transcriptional regulation by a secreted morphogen. Accordingly, Frem1 expression paralleled that of the conserved Sonic Hedgehog (Shh) target gene Gli1 in the cNCC mesenchyme . Suggesting direct transcriptional regulation by Shh signaling, we found that Frem1 expression is induced by SHH ligand stimulation or downstream pathway activation in cNCCs and observed GLI transcription factor binding at the Frem1 transcriptional start site during midfacial morphogenesis. Finally, we found that FREM1 is sufficient to induce cNCC proliferation in a concentration‐dependent manner and that Shh pathway antagonism reduces Frem1 expression during pathogenesis of midfacial hypoplasia. Conclusions: By demonstrating that the Shh signaling pathway regulates Frem1 expression in cNCCs, these findings provide novel insight into the mechanisms underlying variation in midfacial morphogenesis. Key Findings: The Sonic Hedgehog signaling pathway regulates Frem1 expression in cranial neural crest cells. Frem1 is expressed in expansive gradients in the cranial neural crest mesenchyme of the embryonic growth centers that form the midface. FREM1 promotes cranial neural crest cell proliferation in a concentration‐dependent manner. Sonic Hedgehog pathway antagonism reduces Frem1 expression during the pathogenesis of midfacial hypoplasia